2022
DOI: 10.1001/jamacardio.2022.2718
|View full text |Cite
|
Sign up to set email alerts
|

Early Mortality in Type A Acute Aortic Dissection

Abstract: ImportanceEarly data revealed a mortality rate of 1% to 2% per hour for type A acute aortic dissection (TAAAD) during the initial 48 hours. Despite advances in diagnostic testing and treatment, this mortality rate continues to be cited because of a lack of contemporary data characterizing early mortality and the effect of timely surgery.ObjectiveTo examine early mortality rates for patients with TAAAD in the contemporary era.Design, Setting, and ParticipantsThis cohort study examined data for patients with TAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…The two-year survival rate was estimated at 77%; very positive outcomes, especially when considering the poor prognosis of type A dissection medical management [ 33 ]. Laser fenestration can provide a therapeutic option in the context of the emergency management of complex aortic pathology in patients considered unfit for any other surgical or interventional repair [ 34 ]. In this review, the specific anatomical characteristics of type A dissection treated with in situ laser fenestration were lacking while type A aortic dissection repair was mainly performed, as a second stage procedure, in the distal part of the ascending aorta, with a proximal sealing in a “non-diseased” area.…”
Section: Discussionmentioning
confidence: 99%
“…The two-year survival rate was estimated at 77%; very positive outcomes, especially when considering the poor prognosis of type A dissection medical management [ 33 ]. Laser fenestration can provide a therapeutic option in the context of the emergency management of complex aortic pathology in patients considered unfit for any other surgical or interventional repair [ 34 ]. In this review, the specific anatomical characteristics of type A dissection treated with in situ laser fenestration were lacking while type A aortic dissection repair was mainly performed, as a second stage procedure, in the distal part of the ascending aorta, with a proximal sealing in a “non-diseased” area.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another study of 5611 patients showed 48-hour mortality to be 4.4% in patients undergoing emergent repair vs 23.7% in medically managed patients. 5 When cardiac surgery is not immediately available or for patients with complicated ATAAD, transferring patients to a comprehensive aortic 6 For patients with TBAD, the guideline recommends a stepwise approach to confirm organ malperfusion or other indications of complicated disease. Malperfusion is defined as end-organ ischemia and may follow visceral, kidney, spinal, and/or extremity hypoperfusion.…”
Section: Evidence Basementioning
confidence: 99%
“…A study of 2952 patients with ATAAD showed in-hospital mortality associated with emergent surgery to be 19.7% vs 57.1% for patients managed medically ( P < .001) . Another study of 5611 patients showed 48-hour mortality to be 4.4% in patients undergoing emergent repair vs 23.7% in medically managed patients . When cardiac surgery is not immediately available or for patients with complicated ATAAD, transferring patients to a comprehensive aortic center is associated with improved outcomes.…”
Section: Evidence Basementioning
confidence: 99%
“…Therefore, this study aimed to (1) demonstrate operative outcomes in patients requiring long-distance transfer and (2) analyze the effectiveness of helicopter transfer and cloud-type imaging transfer systems in patients suffering from AADA.…”
Section: Introductionmentioning
confidence: 99%